Penyimpanan Awan Sebagai Penyimpanan Digital Bagi Santri Pesantren Tahfidz Quran As-Sholah Gunung Sindur Bogor - Cholis Hanifurohman; Rengga Herdiansyah; Debby Rahadian Baskhara (CV. Multi Kreasi Media, 2023)
In realizing one of the lecturer's tasks, namely the Tri Dharma of higher education at Pamulang University, the team of service lecturers carried out Community Service activities (PKM). Community Service is carried out as a service to the community in the form of the application of science and technology so as to contribute and progress to society. This community service is entitled